2005
DOI: 10.2169/internalmedicine.44.805
|View full text |Cite
|
Sign up to set email alerts
|

Facial Axis Angle as a Risk Factor for Obstructive Sleep Apnea

Abstract: Objective Many Japanese patients with obstructive sleep apnea (OSA) are less obese than Caucasian OSA patients despite their similar severity of OSA, suggesting that their etiology of OSA may differ. The purpose of this study was to identify bony factors associated with OSA in the Japanese population.Methods The clinical records of study subjects were retrospectively reviewed, and cephalometric measurements based on Sella-Nasion references and the Ricketts method were statistically compared.Patients Two hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 24 publications
4
21
2
Order By: Relevance
“…23 Furthermore, the dolico facial pattern and obesity seen in Japanese men were the most important risk factors for OSA patients. 8 The difference between our results and the above cited results is seen in two aspects. First, both reports used a cephalometric Rickett's type of analysis.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…23 Furthermore, the dolico facial pattern and obesity seen in Japanese men were the most important risk factors for OSA patients. 8 The difference between our results and the above cited results is seen in two aspects. First, both reports used a cephalometric Rickett's type of analysis.…”
Section: Discussioncontrasting
confidence: 92%
“…These findings support the view that obesity is one significant risk factor for Malay OSA patients that is in good agreement with findings obtained in the Chinese 5 and Japanese populations. 8 Clinical examination findings indicate that convex profiles, Class II malocclusion, and V shape palatal arch were the most frequent features among Malay OSA patients. It has been found that Japanese adults and children with OSA possess dolico facial patterns (long facial type) with retruded mandibles on Rickett's analysis.…”
Section: Discussionmentioning
confidence: 93%
“…Consistent with their findings, the mean neck circunference in patients with AHI bellow 5 was 35.4 cm and in patients with AHI over 5, the mean values were over 40 cm. All values of vertical facial measurements in this study were higher in the group with AHI over 5, indicating that a long face may contribute to the narrowing of the upper airways space 7,11,12,24,30 . Our predictive model for AHI over 5 indicated that the larger the measures of Tr-Gla, Sn-Me and N.C., the greater would be the likelihood of having OSA.…”
Section: Discussionmentioning
confidence: 51%
“…We also showed that the "underweight" group had higher AHI and a higher proportion of moderateto-serious OSAHS (AHI≥15) patients of both sexes than the normal weight groups. This finding may be unique to Asian OSAHS patients, as nonobese Asian patients have been reported to exhibit relative narrowing of the upper airway due to craniofacial bony structure and the soft tissue of the naso-and oro-pharynx, which may be associated with the development of OSAHS [18,19].…”
Section: Discussionmentioning
confidence: 88%